Statistical Models in Growth Studies of Rabbit - Manojkumar K (Department of Agricultural Statistics, College of Horticulture, 1997)
An investigation was undertaken in the Kerala Agricultural University Rabbit Research Station, Mannuthy to find a suitable relationship between age and body weight of three different breeds of rabbit viz. Newzealand White, Soviet Chinchilla and Grey Giant and to study the impact of climatic elements, temperature and humidity on body weight. The rabbits were reared under uniform feed formula and identical management practices. The investigation mainly depended on data consisting of weekly body weights of rabbits up to twelve weeks and daily climatological parameters, temperature and humidity. The experiment was conducted during the three time periods (First time period: October to January, Second time period: February to May and Third time period: June to September). Seven mathematical models such as linear, quadratic, von-bertalanffy, exponential, modified exponential, logistic and gompertz were fitted for body weights of individual rabbit as well as average body weights over twelve weeks and these models were compared using coefficient of determination (R2) and standard error of estimate (s). Additive model, Wt = a + b L + c G and Multiplicative model, Wt = a Lb GC were fitted for developing a suitable relationship of average body weights, body lengths and body girths over twelve weeks of the three breeds. Using the average weekly dry bulb temperature and wet bulb temperature, Temperature Humidity Indices [THI = 0.72 (Cdb + Cwb) + 40.6 ] were worked out. Correlation coefficients between average daily weight gain per week and THI were worked out for finding the effect of climatological data on body weight. The investigation was having the following salient features. 1. In the time period, October to January the body weight of Newzealand White is significantly different from that of Soviet Chinchilla and Grey Giant. New Zealand White has lower body weight. But the difference-in body weights between Soviet Chinchilla and Grey Giant was not significant. In the second time period, February to May and in the third time period, June to September the difference in body weights of three breeds were not significant. 2. Von bertalanffy model, Wt = a [1 - b Exp(kt)]3 was the most suitable for ascertaining growth in the three breeds of rabbits on individual basis as well as on the basis of average body weights over twelve weeks. 3. The multiplicative model, Wt = a Lb Gc was obtained as the suitable relationship of body weight, body length and body girth of the three breeds of rabbit. 4. During the periods October to January (Winter) and June to September (Monsoon), temperature and humidity had significant effect on body weight. In the former period body weight will decrease along with increase in temperature and in the later period it will increase along with temperature.